АУГМЕНТАЦІЯ ТА ЕЛІЗІЯ У СЛОВОЗМІННИХ ПАРАДИГМАХ ДІЄСЛОВА СТАРОУКРАЇНСЬКОЇ МОВИ XVIII СТ. - Русаченко, Н.П. (Studia Philologica, 2014)
The importance of linear modification of stems in inflectional paradigms of verb in old Ukrainian language in the XVIII centuries is indicated in the article. The nature, the specificity of augmentations and elisions in verbal inflection are characterized. The regularity and functional filling of accretions and truncations of verb stem in old Ukrainian texts are defined.